2016
DOI: 10.1177/194008291600900217
|View full text |Cite
|
Sign up to set email alerts
|

Floristic Composition and Edge-Induced Homogenization in Tree Communities in the Fragmented Atlantic Rainforest of Rio De Janeiro, Brazil

Abstract: This study investigates the changes of tree species composition and diversity along the gradient from fragment edge to interior, and between edge and interior habitats, on a regional scale, in nine Atlantic forest fragments (6-120 ha), in southeastern Brazil. A total of 1980 trees (dbh ≥ 5 cm) comprising 252 species, 156 genera and 57 families were surveyed using the point-centered quarter method. From the fragment edge towards the interior the proportion of shade-tolerant trees increased continuously. The maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 83 publications
(133 reference statements)
2
25
0
2
Order By: Relevance
“…At the local‐scale, we found that both the mean and range of leaf economic trait‐complex values increased from the patch interior toward the edge, implying that species (on average) have higher photosynthetic capacity and a more diverse range of light‐use strategies at edges. This pattern agrees with the observation that edges generally have higher light availability (Matlack , Gehlhausen et al ) and soil nutrients, such that edges tend to favour pioneer species with acquisitive light‐use strategies (Benchimol and Peres 2015, Thier and Wesenberg ). Moreover, high light environments are expected to allow the coexistence of species with diverse light‐use strategies (Ries et al , Shen et al ).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…At the local‐scale, we found that both the mean and range of leaf economic trait‐complex values increased from the patch interior toward the edge, implying that species (on average) have higher photosynthetic capacity and a more diverse range of light‐use strategies at edges. This pattern agrees with the observation that edges generally have higher light availability (Matlack , Gehlhausen et al ) and soil nutrients, such that edges tend to favour pioneer species with acquisitive light‐use strategies (Benchimol and Peres 2015, Thier and Wesenberg ). Moreover, high light environments are expected to allow the coexistence of species with diverse light‐use strategies (Ries et al , Shen et al ).…”
Section: Discussionsupporting
confidence: 88%
“…For the 18 small islands (≤ 1 ha), the whole island was gridded and surveyed, excluding the extreme peripheral zones of the island that were located in the inundation zone. For the 11 larger islands (1.16–1158.09 ha), one to four transects 40 m in width were sampled from the forest edge to forest interior (transect lengths varied from 40 to 210 m, depending on island size; Hu et al ). The FDPs were divided into 10 × 10 m subplots, then further divided into 5 × 5 m (projected area) quadrats.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations